LEGAL FRAMEWORKS FOR CIVIC PARTICIPATION IN PUBLIC SAFETY: CASE OF JAPAN’S TONARI-GUMI AND KOBAN - Urazbaev Abatbay Askerbaevich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:Japan’s public safety model, integrating tonari-gumi volunteer patrols and  Koban  police  stations,  exemplifies  decentralized  governance,  blending  civic participation with institutional oversight. This study analyzes their evolution from 2010 to 2023, assessing legal, economic, and social efficacy amid urbanization (91% urban population),  an  aging  demographic  (38.4%  over  65),  and  rising  cybercrime  (27% increase, 2020 – 2023) [1, 2]. Drawing on National Police Agency data, the research quantifies a 30.2% crime drop (1,897 to 1,324 cases per 100,000), with petty crime falling 82.3% rural and 58.6% urban, though serious crime declined only 23.1% [3]. Historical roots trace to Edo’s gonin-gumi, while post-1947 "Local Autonomy Law" scaled  Koban  to  6,298  and  tonari-gumi  to  46,127  by  2023  [4,  5].  Case  studies (Yamagata,  Fukuoka,  Nagano)  and  55-act  legal  analysis  reveal  adaptability  –  e.g., Fukuoka’s "SafeLink" cut response times from 9.7 to 7.9 minutes – yet privacy lawsuits (52 in 2023) and elderly reliance (42.8% Nagano volunteers over 65) pose challenges [6, 7]. The study highlights "safety social capital" (85.2% rural trust) and explores export potential to regions like Central Asia [8, 9].